The Role of Consumer's Self-Congruence in the Formation of Brand Attitude - Ali Mohamad Rezza (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
This study examines the brand attitudes of smartphone user. In particular, it examines how users self-image congruence can affect their brand attitudes towards smartphone products. Previous research indicates that self-congruence can facilitate positive behavior and attitude towards products. This research used cross-sectional survey explanatory method and structural equation modelling approach to test the hypothesis. A questionnaire was sent to 200 smartphone users in Bandung. Results indicate that self' congruence was a good predictor of user's brand attitude. Keywords: Brand Attitude, Self-image Congruence, Smartphone Market, Consumer Study